Application of The Marketing Mix Model in Consumer Behavior Analysis and Its Educational Implications: Case Study of Specialty Organic Coffee at Waroeng Kopi Kayumas - Nia Rahmi Setiawati; Abdul Wahib Muhaimin; Agustina Shinta Hartati Wahyuningtyas (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the influence of the marketing mix on consumer purchasing decisions for specialty organic coffee at Waroeng Kopi Kayumas in Situbondo Regency. It also examines how consumer attitudes and purchase intentions mediate this relationship. Using an accidental sampling method, data were collected from visitors at the café. The results indicate that while the marketing mix does not directly affect purchase decisions significantly, it has a strong and significant impact on consumer attitudes and purchase intentions. In turn, both these factors significantly influence purchasing decisions. Furthermore, the marketing mix indirectly affects purchase decisions through its influence on attitudes and intentions. These findings contribute to a deeper understanding of consumer behaviour, particularly in niche markets like organic products. They also offer practical and educational value providing a model that can be applied in teaching consumer decision-making, marketing strategies, and sustainability practices in agribusiness and entrepreneurship education